INCREASING THE COMPETITIVENESS OF THE FOOD INDUSTRY BASED ON INNOVATIVE MARKETING STRATEGIES (Marketing Journal, 2026)
This article examines the economic mechanisms and significance of using innovative marketing strategies to enhance the competitiveness of food industry enterprises. As a result of the study, a conceptual model of an innovative marketing strategy for food e nterprises has been developed based on an integrated approach that combines artificial intelligence, big data analytics, and digital marketing tools. The directions for the practical application of the proposed strategic approaches in the food industry of Uzbekistan have been identified.
Keywords: food industry; marketing innovations; competitiveness; artificial intelligence; big data; digital marketing; customer relationship management